2018
DOI: 10.1002/bit.26773
|View full text |Cite
|
Sign up to set email alerts
|

Parsing in vivo and in vitro contributions to microcrystalline cellulose hydrolysis by multidomain glycoside hydrolases in the Caldicellulosiruptor bescii secretome

Abstract: Six multidomain glycoside hydrolases (GHs), CelA (Athe_1867), CelB (Athe_1859), CelC (Athe_1857), CelD (Athe_1866), CelE (Athe_1865), and CelF (Athe_1860) are encoded in the Caldicellulosiruptor bescii glucan degradation locus (GDL). Each GH was affinity-tagged, overexpressed, and purified from recombinant C. bescii for side-by-side characterization in vitro and to examine the contribution of each of these enzymes to microcrystalline cellulose hydrolysis in vivo. All six recombinant GDL GHs were glycosylated, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 46 publications
0
30
0
Order By: Relevance
“…3). Prior in vitro biochemical analyses on the synergy of cellulase mixtures from C. bescii had observed that a mixture of three cellulases, CelA, CelC and CelE (ACE cellulases) worked synergistically to hydrolyze cellulose as well as a mixture of all six C. bescii cellulases [21]. One could hypothesize, then, that members of the genus Caldicellulosiruptor that possess all three of these enzymes would be among the most cellulolytic.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…3). Prior in vitro biochemical analyses on the synergy of cellulase mixtures from C. bescii had observed that a mixture of three cellulases, CelA, CelC and CelE (ACE cellulases) worked synergistically to hydrolyze cellulose as well as a mixture of all six C. bescii cellulases [21]. One could hypothesize, then, that members of the genus Caldicellulosiruptor that possess all three of these enzymes would be among the most cellulolytic.…”
Section: Resultsmentioning
confidence: 99%
“…Three additional species, C. kronotskyensis , C. danielii , and C. naganoensis also share a similar organization of their GDL [36], including the presence of CelA, CelC and CelE. The contributions of CelD and CelF to cellulose hydrolysis or solubilization are low [22,21] and likely not to impact the ability of C. changbaiensis to efficiently hydrolyze cellulose.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A distinguishing feature of the genus Caldicellulosiruptor is the variety of glycoside hydrolases (GHs) encoded in its species' genomes, several of which have multiple domains and multiple catalytic sites. These GHs are designed to degrade complex carbohydrates in the plant cell wall at temperatures greater than 70°C and are either tethered to the bacterium's surface (S)‐layer through an S‐layer homology domain (SLH) or released into the secretome . The GHs responsible for the majority of extracellular cellulose and lignocellulose degradation are concentrated in a single genomic region, termed the glucan degradation locus (GDL) .…”
Section: Introductionmentioning
confidence: 99%
“…The GHs responsible for the majority of extracellular cellulose and lignocellulose degradation are concentrated in a single genomic region, termed the glucan degradation locus (GDL) . Several full‐length enzymes or individual GH domains from the GDL of species, including C. bescii and C. saccharolyticus , have previously been characterized . These GHs in the GDL contain multiple carbohydrate binding module Family 3 (CBM3) domains, interspersed among catalytic domains.…”
Section: Introductionmentioning
confidence: 99%